A Study on the Current Situation of Stigma and Its Influencing Factors Among Chinese Patients with Port-Wine Stains - Ran X; Yang X; Lin X; Yu W; Shang Y; Liang J; Shen L (Clinical, Cosmetic and Investigational Dermatology)
Xuehui Ran,1 Xia Yang,1 Xiaoxi Lin,2 Wenxin Yu,2 Ying Shang,3 Junyan Liang,3 Lingyue Shen1,3 1Department of Oral Maxillofacial Surgery, Shanghai Jiao Tong University School of Medicine Affiliated Ninth People’s Hospital, Shanghai, People’s Republic of China; 2Department of Plastic and Reconstructive Surgery, Shanghai Jiao Tong University School of Medicine Affiliated Ninth People’s Hospital, Shanghai, People’s Republic of China; 3Department of Laser and Aesthetic Medicine, Shanghai Jiao Tong University School of Medicine Affiliated Ninth People’s Hospital, Shanghai, People’s Republic of ChinaCorrespondence: Lingyue Shen, Email sharyshen@qq.com Junyan Liang, Email 466298596@qq.comBackground: Port-wine stains (PWS) are obvious skin lesions, most commonly located on the face and neck, which may lead to varying degrees of stigma in patients. In Chinese culture, where facial appearance is strongly tied to social identity, the stigma associated with PWS may be particularly intense. However, there is no study which examined stigma among Chinese patients with PWS yet.Objective: This study aims to preliminarily investigate the stigma experienced by Chinese patients with facial and cervical PWS and analyze potential contributing factors.Methods: This post-test-only one-group study included 113 adult PWS patients from Aug to Dec 2022 at Shanghai Ninth People’s Hospital. Excluding those with severe psychiatric or cognitive issues. Participants completed demographic, SSCI, SIS, and SES questionnaires. Without a control group or pre-test data, the study reflects real-world clinical settings and patient perceptions post-treatment.Results: Statistical analyses included univariate and multiple linear regression, with Pearson correlations assessing links between stigma and self-esteem. PWS patients’ SSCI, SIS, and SES scores were 50.61± 22.2, 48.71± 15.17, and 24.75± 4.92. PWS size and income were associated with stigma; income and absence from school/work with self-esteem (P < 0.05). In multivariate analysis, only treatment number and PWS type remained significant (P < 0.05). All SSCI dimensions and SIS scores were significantly correlated with self-esteem (P < 0.01).Conclusion: Chinese patients with port-wine stains (PWS) generally experience high levels of stigma and low levels of self-esteem. This study found that the factors influencing stigma among Chinese patients include the type of lesion (flat/thickened) and the number of treatments; an increase in the number of treatments may help alleviate patients’ feelings of stigma. The results suggest that clinical practice should emphasize patients’ emotional experiences and explore comprehensive intervention strategies to promote their mental health.Keywords: port-wine stain, stigma, self-esteem, Chinese patients